Effect of neem (Azadirachta Indica) fibers on mechanical, thermal and durability properties of adobe bricks - Colbert Babé (Elsevier, 2021)
Neem fibers are traditionally added as reinforcements in adobes. Laboratory experiments including, compressive strength, three-point bending strength, water absorption, erosion and thermal conductivity were carried out on adobes made with soil and reinforced with two neem fibers types (straw and leaves) at 0, 1, 2, 3 and 4%. It has been found that mechanical, thermal, and durability properties of adobes were globally improved. Furthermore, leaves neem fibers contribute strongly in comfort thermal, but their use has a negative effect on durability. Nevertheless, adobes reinforced with neem fibers are suitable as building materials with substantial thermal comfort and environmental benefits.